STATUS OF SMALL PELAGIC FISHERY IN THE MAKASSAR STRAIT BASED AT THE NORTHERN PART OF JAVA - Sri Turni Hartati; Setiya Triharyuni; Lilis Sadiyah (Indonesian Fisheries Research Journal, 2016)
The coastal of Makassar Strait is one of main fishing grounds for purse seine vessels from northern part of Java which based at the following landing sites, i.e. Pekalongan, Tegal and Juwana. The purse seine fishery predominantly targets small pelagic fish. This paper attempts to present the current condition of small pelagic fishery in the Makassar Strait. Catch and effort (trip) data between 2004 and 2011 from the three landing sites were used to estimate Maximum Sustainable Yield (MSY) using Schaefer & Fox models. The results showed a decreasing trend in the catch rate, from 30.83 tons/trip in 2004 to 12.27 tons/trip in 2011. The estimated MSY is at the range of 34,705- 37,930 tons with optimum efforts for 2,234-2,500 purse seine trips. Thus the level of purse seine fishing effort in 2011, i.e. 3,078 trips, was exceeding the optimum effort. The decreasing trend in the catch rate may indicate overfishing is occurring between 2004 and 2011. For management of the small pelagic fisheries in the waters of Makassar Strait, important action recommended is fishing effort restrictions. The effort allowed would be only in the range of 2,234-2,500 purse seine trips, and the fishing capacity needs to be controled.